The effect of immigration on the German housing market - Umut Unal; Bernd Hayo; Isil Erol (Philipps-University Marburg, School of Business and Economics, 2022)
This study provides evidence of the causal impact of immigration on German house prices, flat prices, and flat rents using an extensive dataset covering 382 administrative districts over the period 2004-2020. Employing a panel-data approach and a manually constructed shift-share instrument, we show that international migration has a significantly positive short-term effect on German flat prices and rents. House prices are not significantly affected. We estimate that an increase in international migration of 1% of the initial district population causes a hike in flat prices of up to 3% as well as a hike in flat rents of about 1%. The increase in flat prices is more than twice as high as this at the lower end of the market, whereas the flat rental market demonstrates a more linear response. We also discover that immigration's impact on flat prices and rents does not significantly differ across rural and urban areas within the country.
Keywords: J61; R23; R31; 330; Immigration; Housing prices; Rents; Instrumental variable; IV quantile regression; Germanhousing market